2022
DOI: 10.3389/fimmu.2022.1016268
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics reveals small RNA composition and differential microRNA responses underlying interferon-mediated antiviral regulation in porcine alveolar macrophages

Abstract: Previous studies have shown that interferon-mediated antiviral activity is subtype-dependent. Using a whole transcriptome procedure, we aimed to characterize the small RNA transcriptome (sRNA-Seq) and specifically the differential microRNA (miRNA) responses in porcine alveolar macrophages (PAMs) upon antiviral activation during viral infection and interferon (IFN) stimulation. Data showed that near 90% of the qualified reads of sRNA were miRNAs, and about 10% of the other sRNAs included rRNA, snoRNA, snRNA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Our recent research used an infectious DNA clone of the PRRSV-P129 for virus replication-competent expression of a cohort of optimized subtypes of porcine IFNs based on a functional characterization of their antiviral responses. As expected, these MLV-129p-IFN constructs induced comparable or better protection compared with a commercial vaccine in grower pigs regarding the body temperature, lung lesion score, and virus titer, as seen in [82,83] (and unpublished data). Furthermore, these studies also profiled signature gene-responsive pathways using transcriptomic analyses in the livers of pigs vaccinated with MLV-129p-IFNmix to reveal an obtained IFN response mediated by the virus replication-competent expression of IFNs in vivo [82].…”
Section: Interferon Response In Prrs Vaccine Studiessupporting
confidence: 73%
“…Our recent research used an infectious DNA clone of the PRRSV-P129 for virus replication-competent expression of a cohort of optimized subtypes of porcine IFNs based on a functional characterization of their antiviral responses. As expected, these MLV-129p-IFN constructs induced comparable or better protection compared with a commercial vaccine in grower pigs regarding the body temperature, lung lesion score, and virus titer, as seen in [82,83] (and unpublished data). Furthermore, these studies also profiled signature gene-responsive pathways using transcriptomic analyses in the livers of pigs vaccinated with MLV-129p-IFNmix to reveal an obtained IFN response mediated by the virus replication-competent expression of IFNs in vivo [82].…”
Section: Interferon Response In Prrs Vaccine Studiessupporting
confidence: 73%
“…Beyond those central miRNAs within the interaction network, ssc-miR-10b and ssc-miR-9-1 were observed to be upregulated at 3 dpi, and at 7 and 21 dpi, respectively. Both miRNAs are postulated to modify the distinct antiviral reactions triggered by various IFNs in PRRSV-infected PAMs ( 30 ). In our current study, ssc-miR-145-5p, which has been previously observed to induce alternative macrophage priming during PRRSV infection ( 26 ), exhibited a downregulated pattern at 7 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effective prevention or treatment strategies underscores the need for extensive investigations into PRRSV pathogenesis for the discovery of novel vaccines and drugs (1,5), for instance, targeting noncoding RNAs (51). However, previous research in the field has largely centered around limited RNA types and in vitro models, lacking a prolonged infection period (13,(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRRSV primarily infects PAMs and induces apoptosis [ 68 , 69 ]. It has been shown that PRRSV infection of Marc-145 cells, which are derived from African green monkey kidney cells, can regulate apoptosis at different periods of infection [ 70 ].…”
Section: Induction Of Apoptosis By Nsp10mentioning
confidence: 99%